Kingdom of the Netherlands-Netherlands : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Alternate Executive Director for the Kingdom of the Netherlands-Netherlands. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights broad-based economic recovery in the Netherlands, which has been gathering speed. Real growth is forecast to reach 2.1 percent in 2016 owing to strong consumption and investment, reflecting improving confidence and rising housing prices, while net exports are expected to slow as a result of weak external demand. Unemployment has been rapidly declining against the backdrop of an increasing labor supply. The economy is expected to keep its momentum in the coming years. Domestic consumption and investment are forecast to remain the main drivers of growth, prompting a gradual decline in the current account surplus. Inflation is expected to pick up along with the closing of the output gap.